2016
DOI: 10.1039/c6dt00078a
|View full text |Cite
|
Sign up to set email alerts
|

A multimetallic iron(ii)–lithium complex as a catalyst for ε-caprolactone polymerization

Abstract: Treatment of the lithium salt of β-ketimine with FeCl(THF) in the presence of LiN(SiMe) and water affords the multimetallic iron(ii)-lithium complex 1, [(L)Fe]LiO [where L = MeC(O)CHC(NMe)Me]. In complex 1 three separated (L)Fe units are bound together by one LiO species, which leads to the formation of an interesting {FeLiO} core structure. Complex 1 can be used as a single-component initiator for the ring-opening polymerization of ε-caprolactone at room temperature, achieving a monomer conversion of 98% with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Fe(II) and Fe(III) compounds have been proposed as a less toxic alternative to Sn-based catalysts in the ROP of lactones, such as dilactide (Gibson et al, 2002; Wang et al, 2005; Chen et al, 2006; Hege and Schiller, 2014; Geng et al, 2016). The toxicity of tin compounds is related to disturbance of the iron and copper metabolism, as well as the potential denaturation of proteins by reaction with free thiols (Westrum and Thomassen, 2002; Buck et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Fe(II) and Fe(III) compounds have been proposed as a less toxic alternative to Sn-based catalysts in the ROP of lactones, such as dilactide (Gibson et al, 2002; Wang et al, 2005; Chen et al, 2006; Hege and Schiller, 2014; Geng et al, 2016). The toxicity of tin compounds is related to disturbance of the iron and copper metabolism, as well as the potential denaturation of proteins by reaction with free thiols (Westrum and Thomassen, 2002; Buck et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Iron alkoxides have been found to trigger the ring-opening of CL efficiently and to perform chain propagation through a common coordination-insertion mechanism (Scheme ). ,, Earlier studies demonstrated that the activity of iron catalysts toward CL polymerization greatly affected the molecular weight and polydispersity of the products. Fine-tuning the electronic properties of the iron center through modulation of its oxidation state and the design of auxiliary ligands significantly controls the outcome. , To date, well-studied molecular iron alkoxide systems for CL polymerization remain rare, ,,, and the most representative examples are the iron catalysts based on the bis(imino)pyridine ligand , and N , N ′-bis(trimethylsilyl)-benzamidinate …”
Section: Introductionmentioning
confidence: 99%
“…26−29 Finetuning the electronic properties of the iron center through modulation of its oxidation state and the design of auxiliary ligands significantly controls the outcome. 42,47 To date, wellstudied molecular iron alkoxide systems for CL polymerization remain rare, 26,27,30,31 and the most representative examples are the iron catalysts based on the bis(imino)pyridine ligand 31,42 and N,N′-bis(trimethylsilyl)-benzamidinate. 26 As an analogue of a porphyrin scaffold, a dipyrromethene (dipyrrin) framework is a suitable chelating ligand for iron.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As catalysts, iron-based complexes are appealing as iron is earth-abundant and exhibits versatile chemical reactivity . However, the few iron catalysts reported for lactone polymerizations thus far have exhibited low activities and/or yielded broad molecular weight distributions (polymerizations of lactide and cyclic carbonates have also been reported ,, ). Nevertheless, iron-based systems remain of special interest because they offer unique opportunities for tuning of the catalyst spin state, overall charge, and oxidation stateeither of the metal or the ligandover a broad range of accessible redox potentials.…”
Section: Introductionmentioning
confidence: 99%